Tecnología Voip y su impacto en el servicio de Comunicación en los Colegios del Distrito San Hilarión, Provincia de Picota, Región de San Martín - Cabrera Bardales, Jorge (2015)
This thesis, "VOIP TECHNOLOGY AND ITS IMPACT ON COMMUNICATION SERVICE IN SCHOOLS DISTRICT SAN Hilarion, PROVINCE OF STOCKS, San Martin region"; general objective, measuring the impact of the implementation of the VOIP technology in the communication service schools in the district of San Hilarion province of Picota, San Martin region.It also has the following objectives: analyzing communication services in schools in the district of San Hilarion; implement the communications network between the schools of the district of San Hilarion with VoIP technology and measure the results of the implementation of VoIP technology. For the development of the proposed different methodologies were used. For information gathering techniques of observation, interviews were conducted, as well as review and assessment documents for the implementation of VoIP technology which improved communication services schools in the district of San Hilarion province of Picota, region St. Martin. In the following chapters we can closely observe the development of this proposal